Pulsed field gel electrophoresis reveals chromosome length differences between strains of Cladosporium fulvum (syn. Fulvia fulva) - Talbot, N.; Coddington, A.; Oliver, Richard (1991)
Methods are described for the electrophoretic separation of chromosome-sized DNA molecules from the fungal tomato pathogen Cladosporium fulvum (syn. Fulvia fulva). Using a hexagonal electrode array and switching times of 75 min at 45 V for 14 days, nine bands could be resolved. By comparison with co-electrophoresed Aspergillus nidulans chromosomal DNA (which was resolved into seven bands), the sizes of the C. fulvum bands are estimated to be between 1.9 Mb and 5.4 Mb. The two largest bands are believed to be doublets, giving a minimum genome size of 44 Mb. Cloned probes for the ribosomal DNA repeat, an anonymous single copy fragment and a newly discovered retrotransposon were hybridized to blots of the pulsed field gels, demonstrating the use of this technique for genomic mapping. Most strains of C. fulvum had an identical pattern of bands. Two strains exhibited two polymorphisms which could be due to a translocation.